A Strategy to Improve Forward Roll Skills through the STAD Cooperative Learning Model among Junior High School Students: Strategi Meningkatkan Keterampilan Gerak Roll Depan melalui Model Pembelajaran Koperatif Tipe STAD pada Siswa SMP - Ademaya Maemona; Gunawan Gunawan; Anwar Anwar (Ainara Journal (Jurnal Penelitian dan PKM Bidang Ilmu Pendidikan), 2025)
This classroom action research (CAR) aimed to improve students’ learning outcomes in forward roll (floor gymnastics) through the implementation of the cooperative learning model Student Team Achievement Division (STAD) for Class VIII students at SMP Negeri 6 Palu. The problem addressed was the low mastery of forward roll skills, with only 40% of students achieving the minimum learning mastery in the pre-cycle. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through observation and assessment of cognitive, affective, and psychomotor outcomes using validated rubrics. The results revealed significant improvements: student mastery increased to 53.3% in Cycle I and 86.7% in Cycle II. Qualitative observations also showed greater activeness, teamwork, and confidence. These findings indicate that the STAD model effectively supports motor-skill development, fosters positive social interaction, and enhances student motivation. This study contributes theoretically by strengthening the link between cooperative learning and psychomotor development and practically by offering teachers an alternative strategy for active, engaging, and safe physical education instruction.